2017
DOI: 10.1039/c6cp07367k
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic intrinsic lattice thermal conductivity of borophane from first-principles calculations

Abstract: Borophene (boron sheet) as a new type of two-dimensional (2D) material was grown successfully recently. Unfortunately, the structural stability of freestanding borophene is still an open issue. Theoretical research has found that full hydrogenation can remove such instability, and the product is called borophane. In this paper, using first-principles calculations we investigate the lattice dynamics and thermal transport properties of borophane. The intrinsic lattice thermal conductivity and the relaxation time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 50 publications
1
31
0
Order By: Relevance
“…It was found that the number of layers had almost no effect on the lattice thermal conductivity of borophene, which was attributed to the negligible effect of interlayer vdW interactions of the multilayer structure. This is similar to black phosphorene and MoS 2 , while it is different from that of graphene with monotonically decreasing of thermal conductivity with the increasing number of layers …”
Section: Thermal Transport Of Borophenementioning
confidence: 68%
See 2 more Smart Citations
“…It was found that the number of layers had almost no effect on the lattice thermal conductivity of borophene, which was attributed to the negligible effect of interlayer vdW interactions of the multilayer structure. This is similar to black phosphorene and MoS 2 , while it is different from that of graphene with monotonically decreasing of thermal conductivity with the increasing number of layers …”
Section: Thermal Transport Of Borophenementioning
confidence: 68%
“…It was explained by the fact that the relaxation time of acoustic branches for C‐borophane is 10 3 −10 4 ps, two order of magnitudes larger than that of δ 6 borophene. Comparing with stanene and arsenene, the thermal transfer of C‐borophane is obviously faster due to higher group velocity although they possess the same order of phonon relaxation time . On the other hand, the thermal conductivity of hydrogenated graphene‐like borophene along armchair and zigzag directions is 293 and 335 W m −1 K −1 , respectively, which is the largest value among all reported 2D borophene sheets to date.…”
Section: Thermal Transport Of Borophenementioning
confidence: 92%
See 1 more Smart Citation
“…The mechanical properties of several borophene sheets have been investigated, and their ideal strength, ultimate strain, and Young’s modulus have been reported [ 16 , 18 22 ]. Superconductivity [ 23 27 ] and thermal conductivity [ 13 , 28 ] of borophene sheets have also been studied. It was predicted that their superconductivity could be modulated by the strain, while their thermal conductivity is low.…”
Section: Introductionmentioning
confidence: 99%
“…Strain and surface functionalization have been proved to be effective on stabilizing the 2D materials. [15][16][17][18][19][20] Penev et al proposed that the imaginary frequencies of both β 12 and χ 3 borophene near the G point may be eliminated by applying a uniform tensile strain. 15 Additional, based on the first-principles calculations, 19,20 Xu et al and Liu et al predict that the fully hydrogenated buckled triangular borophene is dynamical stable without imaginary frequency.…”
Section: Introductionmentioning
confidence: 99%